Diagnostic value of anti-HLA antibody monitoring in the diagnosis of immunological complications following kidney transplantation - V. O. Aleksandrova; I. V. Dmitriev; N. V. Borovkova; A. G. Balkarov; N. A. Mushta; N. V. Shmarina; N. V. Doronina; K. E. Lazareva (Вестник трансплантологии и искусственных органов)
Introduction. Despite improvements in immunosuppressive therapy procedures, immunological complications continue to be a major cause of kidney graft loss. The level of pre-existing and de novo synthesized anti-HLA antibodies (AB) has shown high significance in modern diagnosis of graft rejection and assessment of the efficacy of anti-crisis therapy.Objective: to analyze the frequency and specificity of pre-existing and de novo synthesized (including donor-specific), anti-HLA antibodies, to assess their impact on acute rejection crisis and kidney transplant (KT) outcomes in the early postoperative period.Materials and methods. We retrospectively analyzed the treatment outcomes of 637 patients, who received a deceased-donor kidney transplant at Sklifosovsky Research Institute of Emergency Care from 2020 to 2022. Pre-existing and de novo synthesized anti-HLA AB, including donor-specific antibodies (DSA), were determined and their impact on the incidence of acute rejection crisis (ARC) in the early postoperative period and on kidney graft function was assessed.Results. In non-sensitized patients, the ARC rate was 10.7% (n = 58), primary initial graft function was noted in 354 patients (65.6%), and satisfactory function at discharge was observed in 377 patients (70%). Pre-existing anti-HLA AB was detected in 97 recipients (15.2%); ARC developed in 14 recipients (14.4%) from this group, 51 (52.6%) patients had primary initial function, and 62 (63.9%) exhibited satisfactory function at discharge. De novo anti-HLA AB synthesis after transplantation was noted in 70 (11%) patients, ARC in 10 of them (16.7%), 38 (54.3%) had primary function, and 43 (61.4%) had satisfactory function at discharge. DSA synthesis was detected in 10 patients, ARC was diagnosed in 5 (50%) of them, primary initial function and satisfactory function at discharge were noted in 3 (30%) recipients.Conclusions. The presence of pre-existing and/or de novo anti-HLA AB synthesis after KT under rationally selected immunosuppressive therapy did not statistically significantly affect the early outcomes of graft function. However, DSA synthesis statistically significantly increased the incidence of acute rejection, kidney graft dysfunction and increased the time of recovery of nitrogen excretory function.